Metabolic control of muscle blood flow during exercise in humans - Boushel, R. (Canadian Journal of Applied Physiology, 2003)
During muscle contraction, several mechanisms regulate blood flow to ensure a close coupling between muscle oxygen delivery and metabolic demand. No single factor has been identified to constitute the primary metabolic regulator, yet there are signal transduction pathways between skeletal muscle and the vasculature that induce vasodilation. A link between muscle metabolic events and microvascular control of blood flow is illustrated by local dilation of terminal arterioles during contraction of muscle fibers and conduction of vasodilation upstream. Endothelial-derived vasodilator mechanisms are known to exert control of muscle vasodilation. Adenosine, nitric oxide (NO), prostacyclin (PGI2), and endothelial-derived hyperpolarization factor (EDHF) are possible mediators of muscle vasodilation during exercise. In humans, adenosine has been shown to contribute to functional hyperemia as blood flow is reduced under nonselective adenosine-receptor blockade. No clear role has been demonstrated for either NO or PGI2, based on studies employing selective inhibition of these substances individually, suggesting a redundancy of vasodilator mechanisms. This is supported by recent work demonstrating that combined blockade of NOS and PGI2, and NOS and cytochrome P450, both attenuate exercise-induced hyperemia in humans. Combined vasodilator blockade studies offer the potential to uncover important interactions and compensatory vasodilator responses. The signaling pathways that link metabolic events evoked by muscle contraction to vasodilatory signals in the local vascular bed remains an important area of study.